Deciphering the antimicrobial activity of multifaceted rhizospheric biocontrol agents of solanaceous crops viz., Trichoderma harzianum MC2, and Trichoderma harzianum NBG - Rahman, Mehjebin; Borah, Sapna Mayuri; Borah, Pradip Kr.; Bora, Popy; Sarmah, Bidyut Kumar; Lal, Milan Kumar; Tiwari, Rahul Kumar; Kumar, Ravinder (Frontiers in Plant Science, 2023)
Solanaceae family, generally known to be the third most economically important plant taxon, also especially harbours as a host to several plant pathogens. Diseases like wilt and fruit rot of solanaceous crop cause huge yield losses in the field as well as in storage. In the present study, eight isolates of Trichoderma spp. were obtained from rhizospheric micro-flora of three solanaceous crops tomato, brinjal and chilli plants and were subsequently screened for pre-eminent biocontrol activity against three fungal (Fusarium oxysporum f. sp. lycopersicum, Colletotrichum gloesporoides and Rhizoctonia solani) and one bacterial (Ralstonia solanacearum) pathogen. Morphological, ITS and tef1α marker-based molecular identification revealed the eight isolates as different strains of Trichoderma. Seven isolates were distinguished as T. harzianum while one was identified as T. asperellum. In vitro antagonistic and biochemical assays indicated significant biocontrol activity governed by all the eight isolates. Two fungal isolates, T. harzianum MC2 and T. harzianum NBG were further evaluated to decipher their best biological control activity. Preliminary insights into the secondary metabolic profile of both isolates were retrieved by liquid chromatography-mass spectrometry (LC-MS). Several antifungal and antibacterial compounds were predicted which possibly confer biocontrol properties to the identified isolates. The efficacy of these two strains in suppressing bacterial wilt and promoting plant growth in the tomato crop was also tested in the field. The disease incidence was significantly reduced by 47.50% and yield incremented by 54.49% in plants treated in combination with both the bioagents. The results of scanning electron microscopy were also in consensus with the in planta results. The results altogether prove that T. harzianum MC2 and T. harzianum NBG are promising microbes for their prospective use in agricultural biopesticide formulations.